Genistein partly eases aging and estropause-induced primary cortical neuronal changes in rats. - Tsyr-Jiuan Wang; Jeng-Rung Chen; Wen-Jay Wang; Yueh-Jan Wang; Guo-Fang Tseng (PLoS ONE)
Gonadal hormones can modulate brain morphology and behavior. Recent studies have shown that hypogonadism could result in cortical function deficits. To this end, hormone therapy has been used to ease associated symptoms but the risk may outweigh the benefits. Here we explored whether genistein, a phytoestrogen, is effective in restoring the cognitive and central neuronal changes in late middle age and surgically estropause female rats. Both animal groups showed poorer spatial learning than young adults. The dendritic arbors and spines of the somatosensory cortical and CA1 hippocampal pyramidal neurons were revealed with intracellular dye injection and analyzed. The results showed that dendritic spines on these neurons were significantly decreased. Remarkably, genistein treatment rescued spatial learning deficits and restored the spine density on all neurons in the surgically estropause young females. In late middle age females, genistein was as effective as estradiol in restoring spines; however, the recovery was less thorough than on young OHE rats. Neither genistein nor estradiol rectified the shortened dendritic arbors of the aging cortical pyramidal neurons suggesting that dendritic arbors and spines are differently modulated. Thus, genistein could work at central level to restore excitatory connectivity and appears to be potent alternative to estradiol for easing aging and menopausal syndromes.